2021
DOI: 10.1080/21655979.2021.1955175
|View full text |Cite
|
Sign up to set email alerts
|

Crocin exerts anti-proliferative and apoptotic effects on cutaneous squamous cell carcinoma via miR-320a/ATG2B

Abstract: Cutaneous squamous cell carcinoma (cSCC) is a highly prevalent skin malignancy, and the effective therapy still remains a challenge. Crocin can be used for cSCC therapy. This study explored the effects of cSCC cells treatment with crocin in vitro and in vivo. The study used A431 and SCL-1 cells lines, cSCC human samples and BALB/C nude mice for investigations. Apoptosis was determined by MTT assays, while miR-320a and ATG2B expressions were validated through RT-qPCR. Interaction of miR-320a with ATG2B was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Crocin was reported to play an important role in the regulation of angiogenesis pathways in breast cancer [ 70 ]. Various mechanisms for crocin to suppress cancer cell proliferation and induce apoptosis such as inhibition of key enzymes in nucleic acids synthesis, and remodification of epigenetic properties were suggested by [ 71 ]. In the present study, crocin apoptosis induction and growth arrest in HCC was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Crocin was reported to play an important role in the regulation of angiogenesis pathways in breast cancer [ 70 ]. Various mechanisms for crocin to suppress cancer cell proliferation and induce apoptosis such as inhibition of key enzymes in nucleic acids synthesis, and remodification of epigenetic properties were suggested by [ 71 ]. In the present study, crocin apoptosis induction and growth arrest in HCC was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Xuemei Zhang et al found that methylation of ATG2B CpG island promoter might be associated with the initiation and progression of breast carcinoma [41]. Xiaoqing Bi et al reported that upregulation of ATG2B could inhibit cell proliferation and lead to cell apoptosis in cutaneous squamous cell carcinoma cells [42]. There were also many reports indicating that ATG2B was associated with drug resistance by activating autophagy in multiple tumors [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Xuemei Zhang et al found that methylation of ATG2B CpG island promoter might be associated with the initiation and progression of breast carcinoma (31). Xiaoqing Bi et al reported that upregulation of ATG2B could inhibit cell proliferation and lead to cell apoptosis in cutaneous squamous cell carcinoma cells (32). There were also many reports indicating that ATG2B was associated with drug resistance by activating autophagy in multiple tumors.…”
Section: Discussionmentioning
confidence: 99%